Precision oncogenomics in pediatrics: a personal reflection - Campbell, Cindy (Cold Spring Harb Mol Case Stud, 2018)
Cindy Campbell, a bereaved parent who lost her son to a rare pediatric brain tumor, shares her experience and frustration over the lack of treatment options and minimal research funding in pediatric oncology. She invites Dr. Jeffrey P. Greenfield to reflect on the situation and share his professional experiences pertaining to advances in oncogenomics and pediatric brain tumors. They share a passion for making this technology available to all pediatric brain tumor patients in the future and using data to inform treatment protocols and improve outcomes.